Reducing formaldehyde emissions and enhancing performance of particleboards through the incorporation of activated carbon produced from Scots pine wood residues - Ergün, Mehmet Emin; Koyuncu, Filiz; İstek, Abdullah; Özlüsoylu, İsmail; Özlüsoylu, İsmail; İstek, Abdullah (Wiley, 2025)
Wood-based composite boards present a problem due to formaldehyde emissions from engineered particleboard, which pose health and environmental risks. This study explored the production of activated carbon (AC) from Scots pine (Pinus sylvestris) wood residues using phosphoric acid (H3PO4) as a chemical activator. The process of using waste biomass as raw material for AC production improves waste management and contributes to the circular economy by creating a high-value product from forestry industry byproducts. Activated carbon with a Brunauer-Emmett-Teller (BET) surface area of 1066.46 m2g-1 and a porous structure that enhances adsorption capacity was incorporated into urea-formaldehyde (UF) resin at varying levels (0.0%, 0.5%, 1.0%, and 1.5% by dry weight of the adhesive) for particleboard production. These boards were evaluated for their formaldehyde emissions, physical properties, and mechanical properties. Results showed that adding AC reduced formaldehyde emissions significantly, by up to 50%. The particleboards prepared using the modified resin also demonstrated improved physical and mechanical properties, with a 10% increase in density contributing to enhanced strength and durability. Overall, this approach shows the potential to reduce formaldehyde emissions and improve the sustainability of particleboard production, improving both environmental and human health outcomes.
Keywords: Activated Carbon; Wood Residue; Formaldehyde Emissions; Particleboard